TRADING VOLUME ACTIVITY AND BID-ASK SPREAD BEFORE AND AFTER THE MERGER ANNOUNCEMENT - Lailatul Mubarokah; Agus Sucipto (University of Merdeka Malang, 2011)
Jakarta stock exchange (JSX) and Surabaya Stock exchange (SSX) were the organizers of capital market inIndonesia. Thus, to srengthen the capital market in Indonesia SSX merged into JSX on November 30th, 2007.New information coming into market would influence the trading activities, including trading volume activity(TVA), and bid-ask spread. While, merger also influenced the total issuer of listed companies in Indonesiastock exchange (IDX). This research included an event study with quantitative method about the analysis oftotal issuer differences, TVA and bid-ask spread before and after the merger announcement of SSX into JSX. Itused t-test method and autoregressive distribution lag test. The result of research analysis showed the difference,significance and insignificance. Based on t-test, the total issuer, TVA, and bid-ask spread were notsignificant before and after the merger announcement of SSX into JSX shown by the higher value of sig.2 tailedthan level of significance and value of standard deviation before the merger announcement of SSX into JSXfrom each variable. Based on autoregressive distribution lag test, it showed significant response by hightrading volume of TVA and bid-ask spread and also high volume of buy-offer investor did on several days ofwindows period before and after the merger announcement of SSX into JSX.